Angiotensin for septic shock unresponsive to noradrenaline. Issue 5 (1st May 2000) - Yunge, Mauricio; Petros, Andy
Abstract : Two children with severe septic shock are reported. One had meningococcal septicaemia and the other Escherichia coli septicaemia. They remained hypotensive despite high concentrations of conventional inotropes and vasopressors. In one child, using a pulmonary artery catheter, extended haemodynamic variables were measured. To restore blood pressure, in both cases, an infusion of angiotensin II was used; there was significant improvement in clinical status, resulting in a rapid reduction in the concentration of inotropes required. Both patients successfully survived their septic episodes. Angiotensin II in cases of severe refractory septic hypotension in the paediatric population offers an extra therapeutic manoeuvre.